1995
DOI: 10.1113/jphysiol.1995.sp020846
|View full text |Cite
|
Sign up to set email alerts
|

Failure of P‐glycoprotein (MDR1) expressed in Xenopus oocytes to produce swelling‐activated chloride channel activity.

Abstract: 1. P-glycoprotein, the protein product of the multidrug resistance (MDR1) gene, has ATPdependent transporter activity. It has been suggested that P-glycoprotein may also function as a volume-regulated chloride channel or chloride channel regulator. To assess the chloride channel function of P-glycoprotein, we examined swelling-activated chloride conductances in Xenopusoocytes injected with human MDR1 cRNA. 2. Functional expression of P-glycoprotein in Xenopus oocytes was confirmed using Western blot analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Defolliculated oocytes were thoroughly monitored for endogenous swelling-activated whole-cell currents as reported earlier (33). Three days after injection, oocyte rupture and volume-activated whole-cell currents were virtually absent in waterinjected control oocytes, similar to earlier studies (34). In AQP1-injected oocytes, the hypotonic bath solution activated only a small endogenous whole-cell current before membrane bursting (Fig.…”
Section: Best1 Deficiency In the Mouse Impairs Sperm Function And Resmentioning
confidence: 64%
“…Defolliculated oocytes were thoroughly monitored for endogenous swelling-activated whole-cell currents as reported earlier (33). Three days after injection, oocyte rupture and volume-activated whole-cell currents were virtually absent in waterinjected control oocytes, similar to earlier studies (34). In AQP1-injected oocytes, the hypotonic bath solution activated only a small endogenous whole-cell current before membrane bursting (Fig.…”
Section: Best1 Deficiency In the Mouse Impairs Sperm Function And Resmentioning
confidence: 64%
“…Previously, human MDR1 (Morin et al, 1995) and mouse MDR1b (Castillo et al, 1990) have been expressed functionally in X. laevis oocytes. Here we present the first demonstration of the functional expression of glycosylated BCRP in X. laevis oocytes and provide evidence that the functional form of BCRP in these oocytes is a homodimer with complex substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Ackerman et al [1] reported a 24±2 mV shift in membrane potential when bath chloride was decreased from 103.6 mmol/l to 55.6 mmol/l during hypoosmolality. Whereas their finding suggests the presence of a volume-sensitive Cl -conductance, Morin et al [15] found no shift in zero-current potential under comparable experimental conditions. Again, interindividual differences may account for these conflicting results, showing hyperpolarization (our results), depolarization [1] or no changes [15] upon hypoosmolal challenge of the oocytes.…”
Section: Discussionmentioning
confidence: 90%
“…With regard to X. laevis oocytes, conflicting results exist. Whereas Ackerman et al [1] and Arellano and Miledi [2] described an endogenous Cl -current activated by hypoosmolality, no such current was detected by Morin et al [15]. In contrast, these authors found that a K + conductance contributes to oocyte volume regulation, which others could not find [1,2,6].…”
Section: Introductionmentioning
confidence: 92%